Analysis of Effective Honesty Relationships With Interprofessional Attitudes Through Outbound Activities: Literature Review - Wahyuda, Agus Nur; Sari, Cindy Puspita; Annisa, Gusnita Ayu; Nurhikmah, Nadya; Abdilla, Sintia; Nareswara, Zahra Filloa; Fanani, Erianto; Eryani, Salwa Al; Ugsang Acob, Joel Rey (Tarqabin Nusantara Group, 2023)
Education about interprofessional education is needed by every student, especially for students in the health sector. Collaborative skills can be done by using the outbound method. Doing outbound in nature, for example, is able to improve collaborative abilities in students without leaving their interprofessional nature as a student. Writing this article aims to analyze honesty as an interprofessional factor with outbound games in the form of ball games and trust walks. The writing of this article uses the literature review method with literature searches carried out through esources such as Google Scholar and ResearchGate. The articles obtained were analyzed using a simplified approach, namely by compiling the various articles obtained and simplifying each finding. The results of the literature review show that doing outbound in nature can improve students' collaborative abilities without leaving interprofessional traits. Through outbound activities, character building can also be carried out, one of which is honesty. Focusing on the application of honesty by playing ball games and trust walks in outbound activities can improve student honesty and collaborative skills.